Head over heels [large type] - Orenstein, Hannah (Center Point Large Print, 2021)
"The past seven years have been hard on Avery Abrams: After training her entire life to make the Olympic gymnastics team, a disastrous performance ended her athletic career for good. Her best friend and teammate, Jasmine, went on to become an Olympic champion, then committed the ultimate betrayal by marrying their emotionally abusive coach, Dimitri. Now, reeling from a breakup with her football star boyfriend, Avery returns to her Massachusetts hometown, where new coach Ryan asks her to help him train a promising young gymnast with Olympic aspirations. Despite her misgivings and worries about the memories it will evoke, Avery agrees. Back in the gym, she's surprised to find sparks flying with Ryan. But when a shocking scandal in the gymnastics world breaks, it has shattering effects not only for the sport but also for Avery and her old friend Jasmine"--